Uji Kombinasi Trichoderma dan Kompos terhadap Pembentukan Bintil Akar dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) - Baso Amir; Satria Dermawan (Fakultas Pertanian, Universitas Timor, 2019)
Giving trichoderma and compost is one way to maximize the function of roots and nutrient availability to be absorbed by plants so that it affects plant growth and yield. This study aims to determine the effect of giving trichoderma and compost on the formation of root nodules and peanut crop yields. The study used a Randomized Block Design (RBD) method which consisted of 6 treatments that were repeated 4 times, so that there were 24 experimental units. The treatment consisted of P0: control (without trichoderma and compost); P1: trichoderma 40 grams + 1 kg of compost; P2: trichoderma 60 grams + 1 kg of compost; P3: 80 gram trichoderma + 1 kg of compost; P4: 100 gram trichoderma + 1 kg of compost; P5: 120 gram trichoderma + 1 kg of compost. The parameters observed were number of root nodules, number of active root nodules, number of inactive root nodules, number of pods per plant, pod weight per plant, number of empty pods, number of filled pods, and number of seeds per pod per plant. Observation data were analyzed using SAS software. Analysis using variance analysis (ANOVA) at 5% level. If the results of the analysis of variance showed that there were significant differences between treatments, the analysis was continued with Duncan's multiple range test (DMRT). The results showed that administration of trichoderma and compost with the highest dose (P5: trichoderma 120 gram+1 kg of compost) was among all the best treatments on the number of nodules. While the lowest dose of P1 (trichoderma 40 gram+1 kg of compost) gives the highest yield for the production component (number of pods per plant, pod weight per plant, number of filled pods, and number of seeds per pod per plant).